2022
DOI: 10.1371/journal.pone.0276719
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of non-small cell lung cancer patients after introducing patient navigation: A retrospective cohort study with propensity score weighted historic control

Abstract: OnkoNetwork is a patient navigation program established in the Moritz Kaposi General Hospital to improve the timeliness and completeness of cancer investigations and treatment. The H2020 SELFIE consortium selected OnkoNetwork as a promising integrated care initiative in Hungary and conducted a multicriteria decision analysis based on health, patient experience, and cost outcomes. In this paper, a more detailed analysis of clinical impacts is provided in the largest subgroup, non-small cell lung cancer (NSCLC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The AUC of 0.89 was also higher compared to another study involving a large dataset of electronic health record analysis, which found AUCs ranging from 0.64 to 0.73 [51], when trying to identify patients with delays in starting cancer treatment using patient demographic, clinical, and neighbourhood socio-economic indices. Timeliness of care is important, as it has been shown to be associated with survival, and interventions to improve on the timeliness and completeness of cancer investigations and treatment such as a customised "OnkoNetwork" patient navigation program have been demonstrated to provide for a large survival benefit (HR = 0.63, p = 0.039) [52], but the first important step is to better classify which groups of patients would benefit from such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC of 0.89 was also higher compared to another study involving a large dataset of electronic health record analysis, which found AUCs ranging from 0.64 to 0.73 [51], when trying to identify patients with delays in starting cancer treatment using patient demographic, clinical, and neighbourhood socio-economic indices. Timeliness of care is important, as it has been shown to be associated with survival, and interventions to improve on the timeliness and completeness of cancer investigations and treatment such as a customised "OnkoNetwork" patient navigation program have been demonstrated to provide for a large survival benefit (HR = 0.63, p = 0.039) [52], but the first important step is to better classify which groups of patients would benefit from such interventions.…”
Section: Discussionmentioning
confidence: 99%